The Agroindustry Development Strategy for Java Ijen-Raung Arabica Coffee, in Bondowoso Regency, East Java - Wibowo, Yuli; Purnomo, Bambang Herry; Kristio, Ari (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2021)
AbstractThe potential of Java Ijen-Raung Arabica Coffee in the Bondowoso Regency, East Java needs to be increased by developing the downstream agroindustry. This study aims to determine the location of the downstream coffee agroindustry development area and its potential products, determine the added value of downstream coffee products, analyze its financial feasibility, and formulate a development strategy. Research methods used in this study include factor weighting, exponential comparison method, interpretive structural modeling, Hayami method, and financial feasibility analysis. The results showed that the development of the Java Ijen-Raung Arabica Coffee agroindustry was prioritized in Sumberwringin District as a development center. Downstream coffee products that have the potential to be developed are ground coffee. The added value generated from the processing of ground coffee is IDR 9,320/kg, with a value-added ratio of 48.09%. The results of the financial feasibility analysis show that the downstream coffee agroindustry is financially feasible to be developed by business actors. The downstream agroindustry development strategy formulation for Java Ijen-Raung Arabica Coffee refers to the key development sub-elements, i.e. increasing market area, monitoring product quality, and involving stakeholders in its implementation.Keywords: Bondowoso Regency, downstream agroindustry, Java Ijen-Raung Arabica Coffee, strategy AbstrakPotensi Kopi Arabika Java Ijen-Raung di Kabupaten Bondowoso, Jawa Timur perlu ditingkatkan melalui pengembangan agroindustri hilir. Penelitian ini bertujuan untuk menentukan lokasi wilayah pengembangan agroindustri hilir kopi dan produk potensialnya, menentukan nilai tambah produk hilir kopi, dan menganalisis kelayakannya secara finansial, serta merumuskan strategi pengembangannya. Metode penelitian mencakup pembobotan faktor, metode perbandingan eksponensial, pemodelan struktural interpretatif, metode Hayami, dan analisis kelayakan finansial. Hasil penelitian menunjukkan bahwa pengembangan agroindustri Kopi Arabika Java Ijen-Raung diprioritaskan di Kecamatan Sumberwringin sebagai sentra pengembangan. Produk hilir kopi yang berpotensi untuk dikembangkan adalah kopi bubuk. Nilai tambah yang dihasilkan dari pengolahan kopi bubuk sebesar Rp9.320/kg dengan rasio pertambahan nilai sebesar 48,09%. Hasil analisis kelayakan finansial menunjukkan bahwa agroindustri produk hilir kopi secara finansial layak dikembangkan oleh pelaku usaha. Rumusan strategi pengembangan agroindustri hilir Kopi Arabika Java Ijen-Raung mengacu pada sub elemen kunci pengembangan, yaitu peningkatkan jangkauan pasar, pengawasan kualitas produk, dan melibatkan pemangku kepentingan dalam pelaksanaannya.Kata kunci: agroindustri hilir, Kabupaten Bondowoso, Kopi Arabika Java Ijen-Raung, strategi